Reaksi Pasar Modal Syariah Sebelum dan Sesudah COVID-2019 pada Perusahaan Sub Sektor Pertambangan yang terdaftar dalam Indeks Saham Syariah Indonesia - Amil Fitria; Amalia N. Hidayati (IPM2KPE, 2024)
This research aims to examine differences in returns, abnormal returns and stock trading volume before and after the event of determining COVID-2019 as an Indonesian National disaster in mining sub-sector companies that are members of the Indonesian Sharia Stock Index (ISSI). This research uses a quantitative approach with secondary data collection. Data analysis was carried out using Statistical Product and Service Solutions (SPSS) software version 26, using the paired sample t-test analysis technique. If the data is not normally distributed then use the Wilcoxon test. The results of the research show that there is a significant difference in stock returns before and after the event that declared Covid a national disaster in Indonesia, with a significance value (0.015) lower than the probability value (0.05). This can be seen from the stock return value which decreased over the period of time. observation. Besides that, there is also a significant difference in abnormal returns before and after the event that declared Covid a national disaster in Indonesia, with a significance value (0.000) lower than the probability value (0.05). This can be seen from the abnormal stock return value which decreased over the period of time. observation. However, there is no significant difference in stock trading volume before and after the event that declared Covid a national disaster in Indonesia, with a significance value (0.012) higher than the probability value (0.05). This can be seen from the absence of changes in trading volume during observation period. Keywords: Abnormal Return, Return, Trading Volume Activity